Analisis Unmodifiable dan Modifiable Risk Factors Terhadap Kejadian Hipertensi Pada Lansia di Puskesmas Tungoi - Ningsih, Suci Rahayu; Fauzan, Moh. Rizki (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Hypertension is a degenerative disease usually referred to as the silent killer because sufferers do not know they have hypertension or do not know before checking their blood pressure.  The aim of this study was to analyze the non-modifiable and modifiable risk factors for hypertension.  The research design used by a Cross-Sectional Study .  The sample obtained in this study was 68 people taken by total sampling technique.  The analyzed to measure the relationship between unmodifiable and modifiable risk factor variables on the incidence of hypertension is the chi-square test. The results obtained for unmodifiable risk factors are age (0.002) and heredity (0.014) while the modifiable risk factors are stress (0.003), obesity (0.003), and sodium consumption (0.003) which are associated with the incidence of hypertension. Age and heredity factors cannot be avoided in the risk of hypertension so that hypertension can be controlled with modifiable risk factors such as-avoiding stress and doing lots of physical activity and sedentary behavior can be reduced.